Understanding business intelligence adoption and its values : some examples from Malaysian companies - Ong, In Lih; Siew, Pei Hwa; Wong, Siew Fan * (2011)
Business intelligence (BI) has become increasingly important to organizations in supporting business decision making and in achieving competitive advantage. Often, cases of BI adoption mentioned in the press are those from developed countries such as USA, Australia, and Germany. Seldom are adoption stories from developing countries such as Malaysia being reported. This paper intends to highlight a few BI adoption cases among Malaysian companies from various industries. The goal is to underscore (1) the way these companies make use of different BI capabilities, and (2) the values of BI to the companies. By doing so, it is hoped that more Malaysian companies, regardless of size, will become aware of BI and will adopt and adapt the tools as catalysts to support their businesses.